Mechanism analysis of heavy metal lead captured by natural-aged microplastics. (May 2021) - Fu, Qianmin; Tan, Xiaofei; Ye, Shujing; Ma, Lili; Gu, Yanling; Zhang, Peng; Chen, Qiang; Yang, Yuanyuan; Tang, Yuanqiang
Abstract: In this paper, the mechanism of lead (Pb(II)) captured by natural-aged microplastics in aqueous medium was explored. Compared with pristine microplastics, the natural-aged microplastics were more efficient for adsorbing Pb(II). After treated by hydrochloric acid (HCl) or sodium hydroxide (NaOH), the organic film was damaged and the adsorption efficiency decreased obviously, which proved that the organic film played an important role in Pb(II) capture. The fitting results of the isothermal adsorption model showed that this adsorption process was more in line with Langmuir model than with Freundlich model, and the maximum adsorption amount (13.60 mg/g) could also be obtained from the Langmuir model. Based on the comprehensive analysis of XRD, XPS and FTIR results, it was found that Pb(II) capture by natural-aged microplastics was mainly determined by the oxygen containing functional groups (carboxyl and hydroxyl groups) on the organic film. Besides, the measurement results of Zeta potential and pH effect showed that electrostatic interaction was mainly responsible for the Pb(II) capture process. Highlights: The Pb(II) capture capacity by natural-aged microplastic was higher than pristine one. The q m of Pb(II) captured by natural-aged microplastic was 13.60 mg/g. Natural-aged microplastic formed a layer of organic film on the surface. Oxygen-containing functional groups of organic film contributed to Pb(II) adsorption.